2014
DOI: 10.1021/ie4016073
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation and Adsorption of Elemental Mercury over CuCl2-Impregnated Sorbents

Abstract: CuCl 2 -impregnated sorbents were employed to remove elemental mercury from flue gas. Three carriers including neutral Al 2 O 3 , artificial zeolite, and activated carbon have been investigated in this research. The performances of these prepared sorbents have been tested in a bench-scale fixed-bed reactor under different simulated flue gas atmospheres and temperatures (333−573 K). CuCl 2 -impregnated activated carbon showed the best adsorption ability. However, CuCl 2 -impregnated neutral Al 2 O 3 and zeolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 43 publications
3
48
0
Order By: Relevance
“…An earlier study also confirmed that main peaks of Cu 2p 3/2 were from 926 to 939 eV and Cu + and (Du et al, 2014). Du et al (2014) also showed that after Hg 0 removal test in the simulated flue gas, the spectrum area ratio of Cu + to Cu 2+ increased from 0.19 to 0.45, which should stem from the oxidation of Cu + by the oxidizing flue gas components. The oxidation of impregnated metal oxides is also expected in our test environment, in which great amounts of O 2 and HCl are present.…”
Section: +supporting
confidence: 52%
See 2 more Smart Citations
“…An earlier study also confirmed that main peaks of Cu 2p 3/2 were from 926 to 939 eV and Cu + and (Du et al, 2014). Du et al (2014) also showed that after Hg 0 removal test in the simulated flue gas, the spectrum area ratio of Cu + to Cu 2+ increased from 0.19 to 0.45, which should stem from the oxidation of Cu + by the oxidizing flue gas components. The oxidation of impregnated metal oxides is also expected in our test environment, in which great amounts of O 2 and HCl are present.…”
Section: +supporting
confidence: 52%
“…Liu and Liu (2013) suggested that activated coke doped with V metal oxide had high activities in adsorption and oxidation, which are the key mechanisms for multipollutants removal in coal-fired flue gas. Du et al (2014) indicated that CuCl 2 -impregnated activated carbon had higher adsorption ability for Hg 0 as compared to those for CuCl 2 -impregnated neutral Al 2 O 3 and zeolite at 60-300°C.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Besides sulfur, activated carbon impregnated with metal salts has demonstrated the competitive adsorption performance to those treated with sulfur. Copper salts, such as CuCl 2 and Cu(NO 3 ) 2 , have been extensively investigated as impregnation agents since they can not only increase the adsorption capacity of lowconcentration Hg 0 but also enhance the oxidation of Hg 0 into water-soluble Hg 2+ for activated carbon (Williams et al, 1997;Vidic et al, 2001;Kim et al, 2005;NguyenThanh et al, 2005;Lee et al, 2008;Lee et al, 2009a, b, c;Zheng et al, 2012;Li et al, 2013;Du et al, 2014;Liu et al, 2015;Yang et al, 2016a, b, c, d). Lee et al (2009a) suggested that activated carbon containing CuCl 2 may possess different sites available for Hg 0 oxidation and Hg adsorption, and the resulted oxidized Hg generated from the reactions between Hg 0 and CuCl 2 may be re-adsorbed at other available sites of the CuCl 2 -treated activated carbon.…”
Section: Introductionmentioning
confidence: 99%
“…CuCl 2 modified non-carbon sorbents have been shown to be promising mercury sorbents [15,16]. Copper, a transition metal, may have special catalytic effects for mercury oxidation due to its ability to store/release oxygen via the redox shift between Cu 2+ and Cu + [17].…”
Section: Introductionmentioning
confidence: 99%